EDUCATION METHOD AKHLAK IN SDIT UMMUL QURO - Agus Patoni; Wido Supraha; Anung Al hamat (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This research focuses on the background of morals decline in early childhood caused by lack of attention or supervision of parents and schools towards them. Morals in Islamic civilization is a fence that limits both at the same time the upright foundation upon which the glory of Islam. The basic values of Islam and morals are included in every rule of life, various kinds of differences and their development, both individually, as well as society, politics and economics. This research was formulated to describe the various methods of moral education that are applied at SDIT Ummul Quro. This research is a type of qualitative research Â with a field research approach, aims to explore various methods of moral education through primary and secondary literature relating to the object of research, then integrated with field research in an effort to produce products to be implemented in other institutions. This research resulted in the method of elementary school morals education at the institution, namely: (1) the exemplary method of an educator figure (2) the habituation method was more emphasized to students as recipient subjects (3) the reward and funishment method (reward and sanctions), in the form gift giving and sanctions.Â